Enhanced Oxygen Reduction Stability and Activity by Co and N (or O) Interaction in CoO on N-Doped Carbon Prepared through Spray Pyrolysis - Kim, In Gyeom; Nah, In Wook; Park, Sehkyu (WILEY-V C H VERLAG GMBH, 2018)
Although the development of a highly active and cost-effective electrocatalyst for the oxygen reduction reaction (ORR) is necessary, it is a challenging issue for commercially viable energy conversion applications such as fuel cells or metal-air batteries. In this study, we synthesize nitrogen-doped, carbon-supported CoO catalysts (denoted as CoO/NCs) with high stability and activity. The CoO/NC is prepared by one-pot spray pyrolysis, which is simple and has an easily scalable synthetic route. In an effort to find a better catalyst composition for ORR activity, several catalysts are synthesized by controlling the concentrations of the solutions that contain carbon, urea as the nitrogen source, and a cobalt precursor. The catalysts are then characterized using various methods to comprehensively study their properties coupled with ORR kinetics and stability. The CoO/NC2 catalyst shows higher catalytic activity towards ORR than the other in-house prepared catalysts. It is comparable to commercial Pt/C and has very high stability for 80h in an alkaline medium. Systematic analyses clarify that the superior electrocatalytic performance of CoO/NC2 stems mainly from its enhanced electron density and pathway by heteroatom doping and its modified carbon nature during spray pyrolysis.
Keywords: REDUCED GRAPHENE OXIDE; EFFICIENT BIFUNCTIONAL ELECTROCATALYST; MEMBRANE FUEL-CELLS; EVOLUTION REACTION; REDUCTION/EVOLUTION REACTIONS; CO3O4 NANOPARTICLES; NITROGEN; NANOTUBES; METAL; NANOCOMPOSITES